Impact of hydrogen injection on thermophysical properties and measurement reliability in natural gas networks - Dell’Isola Marco (EDP Sciences, 2021)
In the context of the European decarbonization strategy, hydrogen is a key energy carrier in the medium to long term. The main advantages deriving from a greater penetration of hydrogen into the energy mix consist in its intrinsic characteristics of flexibility and integrability with alternative technologies for the production and consumption of energy. In particular, hydrogen allows to: i) decarbonise end uses, since it is a zero-emission energy carrier and can be produced with processes characterized by the absence of greenhouse gases emissions (e.g. water electrolysis); ii) help to balancing electricity grid supporting the integration of non-programmable renewable energy sources; iii) exploit the natural gas transmission and distribution networks as storage systems in overproduction periods. However, the hydrogen injection into the natural gas infrastructures directly influences thermophysical properties of the gas mixture itself, such as density, calorific value, Wobbe index, speed of sound, etc [1]. The change of the thermophysical properties of gaseous mixture, in turn, directly affects the end use service in terms of efficiency and safety as well as the metrological performance and reliability of the volume and gas quality measurement systems. In this paper, the authors present the results of a study about the impact of hydrogen injection on the properties of the natural gas mixture. In detail, the changes of the thermodynamic properties of the gaseous mixtures with different hydrogen content have been analysed. Moreover, the theoretical effects of the aforementioned variations on the accuracy of the compressibility factor measurement have been also assessed.